Time to Positivity of Cultures Obtained for Periprosthetic Joint Infection. (18th January 2023) - Tarabichi, Saad; Goh, Graham S.; Zanna, Luigi; Qadiri, Qudratullah S.; Baker, Colin M.; Gehrke, Thorsten; Citak, Mustafa; Parvizi, Javad
Abstract : Background: Despite its well-established limitations, culture remains the gold standard for microbial identification in periprosthetic joint infection (PJI). However, there are no benchmarks for the time to positivity (TTP) on culture for specific microorganisms. This study aimed to determine the TTP for pathogens commonly encountered in PJI. Methods: This retrospective, multicenter study reviewed prospectively maintained institutional PJI databases to identify patients who underwent hip or knee revision arthroplasty from 2017 to 2021 at 2 tertiary centers in the United States and Germany. Only patients who met the 2018 International Consensus Meeting (ICM) criteria for PJI and had a positive intraoperative culture were included. TTP on culture media was recorded for each sample taken intraoperatively. The median TTP was compared among different microbial species and different specimen types. Data are presented either as the mean and the standard deviation or as the median and the interquartile range (IQR). Results: A total of 536 ICM-positive patients with positive cultures were included. The mean number of positive cultures per patient was 3.9 ± 2.6. The median TTP, in days, for all positive cultures was 3.3 (IQR, 1.9 to 5.4). Overall, gram-negative organisms (TTP, 1.99 [1.1 to 4.1]; n = 225) grew significantly faster on culture compared with gram-positive organisms (TTP, 3.33 [1.9 to 5.8]; n = 1, 774). Methicillin-resistant Staphylococcus aureus (TTP, 1.42 [1.0 to 2.8]; n = 85) had the fastest TTP, followed by gram-negative rods (TTP, 1.92 [1.0 to 3.9]; n = 163), methicillin-sensitive Staphylococcus aureus (TTP, 1.95 [1.1 to 3.3] n = 393), Streptococcus species (TTP, 2.92 [1.2 to 4.3]; n = 230), Staphylococcus epidermidis (TTP, 4.20 [2.4 to 5.5]; n = 555), Candida species (TTP, 5.30 [3.1 to 10]; n = 63), and Cutibacterium acnes (TTP, 6.97 [5.9 to 8.2]; n = 197). When evaluating the median TTP according to specimen type, synovial fluid (TTP, 1.97 [1.1 to 3.1]; n = 112) exhibited the shortest TTP, followed by soft tissue (TTP, 3.17 [1.4 to 5.3]; n = 1, 199) and bone (TTP, 4.16 [2.3 to 5.9]; n = 782). Conclusions: To our knowledge, this is the first study to examine the TTP of common microorganisms that are known to cause PJI. Increased awareness of these data may help to guide the selection of appropriate antimicrobial therapy and to predict treatment outcomes in the future. Nonetheless, additional studies with larger cohorts are needed to validate these benchmarks. Level of Evidence: Diagnostic Level IV . See Instructions for Authors for a complete description of levels of evidence.